2016
DOI: 10.1016/j.chest.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

ICU-Acquired Weakness

Abstract: Survivorship after critical illness is an increasingly important health-care concern as ICU use continues to increase while ICU mortality is decreasing. Survivors of critical illness experience marked disability and impairments in physical and cognitive function that persist for years after their initial ICU stay. Newfound impairment is associated with increased health-care costs and use, reductions in health-related quality of life, and prolonged unemployment. Weakness, critical illness neuropathy and/or myop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
229
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(271 citation statements)
references
References 85 publications
(74 reference statements)
3
229
1
12
Order By: Relevance
“…After approval had been obtained from the Mayo Clinic institutional review board, we retrospectively identified 58 patients from the Mayo Clinic Rochester and Arizona databases who were diagnosed with CINM, using clinical and electrodiagnostic criteria. [2][3][4][5] We chose to define our experimental cohort operationally as having CINM in light of the high incidence of co-occurrence of CIM and CIP, [8][9][10][11][12] because of the difficulty in definitively distinguishing the entities clinically and electrophysiologically (particularly in mild cases of CIM and/or CIP) in the ICU environment, and due to the nonstandardized timing of the nerve conduction studies (NCSs) and electromyography (EMG) stemming from the inherent nature of our retrospective study. Nevertheless, we attempted to distinguish between patients who had predominantly CIM versus CIP based on the expert clinician's final diagnosis after synthesizing elements of the history, neurological examination, and electrophysiological testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After approval had been obtained from the Mayo Clinic institutional review board, we retrospectively identified 58 patients from the Mayo Clinic Rochester and Arizona databases who were diagnosed with CINM, using clinical and electrodiagnostic criteria. [2][3][4][5] We chose to define our experimental cohort operationally as having CINM in light of the high incidence of co-occurrence of CIM and CIP, [8][9][10][11][12] because of the difficulty in definitively distinguishing the entities clinically and electrophysiologically (particularly in mild cases of CIM and/or CIP) in the ICU environment, and due to the nonstandardized timing of the nerve conduction studies (NCSs) and electromyography (EMG) stemming from the inherent nature of our retrospective study. Nevertheless, we attempted to distinguish between patients who had predominantly CIM versus CIP based on the expert clinician's final diagnosis after synthesizing elements of the history, neurological examination, and electrophysiological testing.…”
Section: Methodsmentioning
confidence: 99%
“…1 The disease commonly manifests as a flaccid quadriparesis with respiratory weakness and is thought to arise primarily from the downstream effects of systemic inflammation. [2][3][4][5] The term encompasses the entities critical illness polyneuropathy (CIP) 6 and critical illness myopathy (CIM), 7 which commonly co-occur along a proportional spectrum in the individual patient. [8][9][10][11][12] Prompt and accurate recognition of CINM is important to avoid unnecessary workup, to provide prognostic information to families, and to ensure that measures are employed to reduce risk factors.…”
Section: Accepted 18 June 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…Bersano E 1 , Dalla Bella E 1 , Consonni M 1 , Pensato V 2 , Gellera C 2 , Lombardi R 3 , Lauria G 1,3 ruled out malignancies. Treatment with rituximab was withdrawn because of severe allergic reaction; IVIG provided benefit on sensory symptoms.…”
Section: A Case Of Neuropathy With Anti-myelinassociated Glycoprotienmentioning
confidence: 99%
“…The burden of recovery after critical care has both physical and psychosocial dimensions. Symptoms of intensive care unit acquired weakness (ICUAW) are among the most commonly reported physical health limitations, and up to 80% of ICU patients develop some kind of neuromuscular dysfunction (Jolley, Bunnell, & Hough, 2016).…”
Section: Introductionmentioning
confidence: 99%